2013
DOI: 10.1539/joh.12-0189-oa
|View full text |Cite
|
Sign up to set email alerts
|

Change in Lung Function over Time in Male Metropolitan Firefighters and General Population Controls: A 3‐year Follow‐up Study

Abstract: Change in Lung Function over Time in Male Metropolitan Firefighters and General Population Controls: A 3‐year Follow‐up Study: Tjard R. SCHERMER, et al. Discipline of General Practice, School of Population Health, The University of Adelaide, Australia Objective Previous studies in firefighters have been contradictory regarding their course of lung function over time. The aim of this ongoing study is to investigate how changes in lung function over time in male metropolitan firefighters compare with those in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…It implies that as the years of service increases, the lung function parameters decreases proportionately. Our finding is similar to other previously published studies which have also shown a decline in lung function as duration of service increases [4,5,9,10] . Unger et al, demonstrated a trend towards an increased rate of volume loss in the FVC and FEV1 as years progressed, among the fire fighters [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It implies that as the years of service increases, the lung function parameters decreases proportionately. Our finding is similar to other previously published studies which have also shown a decline in lung function as duration of service increases [4,5,9,10] . Unger et al, demonstrated a trend towards an increased rate of volume loss in the FVC and FEV1 as years progressed, among the fire fighters [11].…”
Section: Discussionsupporting
confidence: 93%
“…The pioneering studies on lung function among firefighters were conducted in Boston in the 1970s [3]. Since then many studies have been conducted to assess the acute and chronic effects of smoke on lung function [4][5][6][7][8][9][10]. Acute effects on the lungs have well been documented in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…A more valid means of examining lung function in a population like this is to examine the annual rate of change for each individual and compare this to an established limit of normal longitudinal decline [24]. This is the intention of our surveillance program, and preliminary results have previously been reported [15]. Longitudinal surveillance may also reduce the misclassification of those whose lung function lies close to the LLN or upper limit of normal, given that such classifications can change over follow-up [25].…”
Section: Discussionmentioning
confidence: 99%
“…Only never-smokers and firefighters with no history of doctor-diagnosed asthma or lung disease, based on questionnaire responses, were included in this analysis. Further details of procedures and equipment used in data collection have been previously described [11, 15, 16]. Calibration was performed on a daily basis using a three-litre syringe while zero flow was set immediately before each measurement.…”
Section: Methodsmentioning
confidence: 99%
“…15 Schermer et al (2010) compared the lung function and health of (501) firefighters of a South Australian metropolitan department to the (1324) general population and found better overall general health, lung health, and mental health in the firefighter sample. Schermer et al (2013) extended this work with a three-year follow-up and showed a decline in lung function in firefighters for those who reported incompliance of their respiratory protection. Baris et al (2001) evaluated the mortality of a cohort of 7789 Philadelphia firefighters, employed over 1925 to 1986.…”
Section: Other Occupational Diseasesmentioning
confidence: 77%